1985
DOI: 10.2165/00003088-198510040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Sulphasalazine, Its Metabolites and Other Prodrugs of 5-Aminosalicylic Acid

Abstract: There is accumulating clinical evidence that 5-aminosalicylic acid (5-ASA) represents the therapeutic moiety of sulphasalazine in the treatment of inflammatory bowel disease. For more than 4 decades, the active metabolite, 5-ASA, has been administered in the form of the 'prodrug' sulphasalazine; however, in contrast to sulphasalazine, the pharmacokinetics of 5-ASA were unknown until recently. Sulphasalazine itself is poorly absorbed (3 to 12%) and its elimination half-life of about 5 to 10 hours is probably af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(119 citation statements)
references
References 59 publications
3
110
0
6
Order By: Relevance
“…As anticipated from systemic pharmacokinetics of intrajejunal drug (I) and other observations (16,64), the kinetics of intravenously administered 5-ASA showed that the drug is rapidly cleared from plasma mainly by metabolism (VI). Further.…”
Section: Vi433 Concluding Remarksmentioning
confidence: 78%
See 4 more Smart Citations
“…As anticipated from systemic pharmacokinetics of intrajejunal drug (I) and other observations (16,64), the kinetics of intravenously administered 5-ASA showed that the drug is rapidly cleared from plasma mainly by metabolism (VI). Further.…”
Section: Vi433 Concluding Remarksmentioning
confidence: 78%
“…proved that the 5-ASA-moiety is a n active drug in its own right (8) which supported early proposals on the possibilities for improving the management of CIBD with SASP (27,82). Thus, a rapid development in the field of new 5-ASA drug-formulations with different principles of sustained-release (SR) is now taking place (16,57,64).…”
Section: Prefacementioning
confidence: 99%
See 3 more Smart Citations